Plasticity of the visual system after early brain damage - Guzzetta, A.; D'acunto, G.; Rose, S.; Tinelli, F.; Boyd, Roslyn; Cioni, G. (Wiley-Blackwell Publishing Ltd., 2010)
The aim of this review is to discuss the existing evidence supporting different processes of visual brain plasticity after early damage, as opposed to damage that occurs during adulthood. There is initial evidence that some of the neuroplastic mechanisms adopted by the brain after early damage to the visual system are unavailable at a later stage. These are, for example, the ability to differentiate functional tissue within a larger dysplastic cortex during its formation, or to develop new thalamo-cortical connections able to bypass the lesion and reach their cortical destination in the occipital cortex. The young brain also uses the same mechanisms available at later stages of development but in a more efficient way. For example, in people with visual field defects of central origin, the anatomical expansion of the extrastriatal visual network is greater after an early lesion than after a later one, which results in more efficient mechanisms of visual exploration of the blind field. A similar mechanism is likely to support some of the differences found in people with blindsight, the phenomenon of unconscious visual perception in the blind field. In particular, compared with people with late lesions, those with early brain damage appear to have stronger subjective awareness of stimuli hitting the blind visual field, reported as a conscious feeling that something is present in the visual field. Expanding our knowledge of these mechanisms could help the development of early therapeutic interventions aimed at supporting and enhancing visual reorganization at a time of greatest potential brain plasticity. © The Authors. Journal compilation © Mac Keith Press 2010.